Is the grass always greener on the other side? Foreign work-force expectations and experience of temporary staffing agencies and Icelandic society - Kristjánsdóttir, Erla S.; Christiansen, Þóra H.; Minelgaite, Inga (Research in applied business and economics, 2019)
In the wake of the financial crisis of 2008, developments in the Icelandic economy, such as booming tourism and construction, have triggered a rise in the temporary workforce industry in the country. The majority of the temporary work force in Iceland is from Eastern Europe and other less economically developed countries. Major societal and economic shifts are evidenced by a doubled number of temporary staffing agencies and ten-fold increase in the number of foreign temporary workers in the last two years, however, the phenomena have barely been addressed in research. Furthermore, the expectations of temporary work force in Iceland have not been researched from an organizational perspective. The study employed field survey method to investigate pre-arrival expectations and post-arrival experiences of temporary agency workers. The research focus was on expectations towards temporary staffing agencies and Icelandic society at large. The main findings indicate that the employees had relatively high expectations towards the temporary staffing agency and Icelandic society before arriving in Iceland. Moreover, those arrived indicated many unmet expectations in these respects, even though a few expectations were exceedingly met. The study provides empirical data that can serve as catalyst for expectation management research in temporary work settings and contribute to better integration of foreign temporary workforce, efficiency of diversity management and business outcomes. Í kjölfar hrunsins 2008 hafa aðstæður í íslensku efnahagslífi, svo sem blómstrandi ferðaþjónusta og byggingariðnaður, leitt til fjölgunar starfsfólks sem kemur tímabundið til landsins. Flestir sem sinna tímabundnum störfum hérlendis koma frá Austur-Evrópu og löndum með lítt þróað eða óstöðugt efnahagsástand. Tvöföldun fjölda starfsmannaleiga og tíföldun tímabundinna starfsmanna undanfarin tvö ár bera með sér stórkostlegar breytingar í þjóðfélaginu og viðskiptalífinu, en þrátt fyrir það hefur þessari þróun verið lítill gaumur gefinn í rannsóknum. ...